2016
DOI: 10.1371/journal.pone.0165838
|View full text |Cite
|
Sign up to set email alerts
|

Information Retrieval during Free Listing Is Biased by Memory: Evidence from Medicinal Plants

Abstract: Free listing is a methodological tool that is widely used in various scientific disciplines. A typical assumption of this approach is that individual lists reflect a subset of total knowledge and that the first items listed are the most culturally important. However, little is known about how cognitive processes influence free lists. In this study, we assess how recent memory of use, autonoetic and anoetic memory, and long-term associative memory can affect the composition and order of items in free lists and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Thus, it is possible that during the interviews people indicated only the plants that are part of recent memory. A study on medicinal plants observed that there are temporal limits in the retrieval of information by the interviewees, so that people tend to cite mainly the plants they used in the last year 37 . Thus, memory may have served as a filter, so that, of the plants taught by parents or grandparents outside the context of the settlement, only those occurring on the site were actually mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that during the interviews people indicated only the plants that are part of recent memory. A study on medicinal plants observed that there are temporal limits in the retrieval of information by the interviewees, so that people tend to cite mainly the plants they used in the last year 37 . Thus, memory may have served as a filter, so that, of the plants taught by parents or grandparents outside the context of the settlement, only those occurring on the site were actually mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that diseases considered frequent tend to be associated with a large number of medicinal plants (Santoro et al 2015; Nascimento et al 2016. Sousa et al (2016) found that the species cited first in lists of medicinal plants are those that have been used to treat diseases that have occurred in the last year, and these plants are also considered as more important, but new studies need to be conducted to confirm or not this finding.…”
Section: Local Medical System From the Caatinga And Its Relevance Formentioning
confidence: 99%
“…The elements captured from this question reveal information both about the items mentioned, as well as about the people who listed them, showing remarkable data in a community/culture [5], such as: the importance of items based on the community's consensus (frequency of convergent reports) [6]; the local preference for components used during the interview period of time [7]; the determination of local specialists, since large lists characterize the most knowledgeable people [6], and the listing order of the items, in which those an individual mentions rst are cognitively prominent or "salient" in relation to the last ones [8]. Items's order in lists, together with the number of times the item is cited, serves to calculate the Salience Index [9,10] that determines the cultural relevance of a term or element.…”
Section: Introductionmentioning
confidence: 99%